Taking Children’s Moral Lives Seriously: Creativity as Ethical Response Offline and Online - Kate Ott (Religions, 2019)
Core Christian ethics concepts are affected by assumptions related to the primary subject or moral agent and the social context in which moral encounters take place. This article asks: Are children full moral agents? If so, what can Christian ethics, which predominantly focuses on adult subjects, learn from a focus on children? A small group of Christian ethicists has asked this very question in conversation with psychologists, child development theorists, educators, theologians, and philosophers. Centering children requires attention to age and ability differences and inclusion of their voices. Children as ethical subjects focus attention on issues of particularity, a decentering of rational individualism, and debunking linear moral developmental assumptions. The research on children’s moral lives points toward ethics as creativity in forms of play or improvisation. Given children’s digitally saturated lives, their creative use of critical digital literacies also helps Christian ethics begin to map a response to the impact of digital technologies.